Concreto permeável com agregado reciclado para uso em pavimentação - Oliveira, Iago de (2017)
Civil construction is the activity with the largest volume of solid waste generation in the world, and also responsible for a considerably part of the mineral extraction nowadays. One of the main products of this industry, urban pavements, are usually impermeable, generating water accumulation in urban centres and damaging the natural hydrological cycle. These materials are often dark, contributing to the island heat effect. Aiming to minimize these harmful effects, it is remarkable the importance of research for the development of floors that are permeable, high reflectance, leading recycled waste in its composition and with adequate mechanical resistance to its use. Thus, this work deals with the study of concrete properties with replacement of the virgin aggregate by recycled aggregates, as well as the physical, chemical andmechanical properties of this material. The recycled aggregate used was obtained in the metropolitan region of Curitiba. It was carried out the granulometric characterization of the material, with determination of the powdery material quantity, absorption, specific mass, support index, expansibility, abrasion, index of chlorides and sulphates. A permeable concrete with a high aggregate index was then produced, with different rates of substitution of the virgin aggregate by recycled (0%, 30%, 70% and 100%). In the fresh concrete the slump test was made, and in the hardened material the compressive strength, traction and tensile strength in the flexion, as well as the voids index, absorption, reflectance and permeability were determined. The characterization of the recycled aggregate showed very low contamination rates by sulphates and chlorides, values adequate to the limit established by the Brazilian standard that rules on recycled aggregate for concrete and pavements. Other indexes were also compared to the standard and meet the requirements, such as coefficient of non-uniformity, expandability and abrasion. Also, all concrete tests were evaluated in relation to the replacement of the natural aggregate with recycled material. As a result, there was a decrease in the mechanical strength, specific mass and permeability, and an increase in the absorption and voids index. In all compositions, the concrete had a light reflection about 3 times larger than the asphalt. The mechanical strength values, compared to the requirements of the national pervious pavement standard, indicate that the material is suitable for use as permeable concrete and permeable concrete applied on site for both pedestrian traffic and light vehicular traffic, including the composition with 100% recycled aggregate, which presents 86.35% by mass of total recycled content.